Knowledge Representation and Management. From Ontology to Annotation - Charlet, J.; Darmoni, S.J.; Section Editors for the IMIA Yearbook Section on Knowledge Representation and Management (Yearbook of Medical Informatics, 2015)
Objective: To summarize the best papers in the field of Knowledge Representation and Management (KRM).Methods: A comprehensive review of medical informatics literature was performed to select some of the most interesting papers of KRM published in 2014.Results: Four articles were selected, two focused on annotation and information retrieval using an ontology. The two others focused mainly on ontologies, one dealing with the usage of a temporal ontology in order to analyze the content of narrative document, one describing a methodology for building multi-lingual ontologies.Conclusion: Semantic models began to show their efficiency, coupled with annotation tools.
Keywords: Ontology; knowledge representation; annotation